MANUSIA BERKUALITAS DALAM PANDANGAN AL-QUR’AN - Mujiburrohman Mujiburrohman (Universitas Islam Madura, 2018)
Humans are the most fascinating creatures, unique, multi-dimensional creatures, all-encompassing, open-minded, and have great potential. Therefore, Karen Horny (Psychology expert), said that